Cumplimiento de las normas de bioseguridad del personal de salud en el hospital básico Luis Moscoso Zambrano del cantón de Piñas - Apolo Valarezo, Mercy Viviana (2017)
The biosafety rules are a set of procedures aimed at preventing risk factors in the work environment of the health team, currently each health personnel knows them and is obliged to apply them as this will maintain a safe working environment, In spite of this, it is observed that health workers often do not apply them, with hospital waste management being the most common non-compliance. Therefore, this research was carried out with the general objective: To determine the compliance of Biosafety Standards to Health personnel working in the Luis Moscoso Zambrano Basic Hospital, in the Piñas canton. The design of the study was descriptive and non-experimental. The data collection was carried out by means of the application of an observation guide the same one that was done to 48 people that are part of the health team of the Hospital, with the obtained results a diagnostic base was created that was the starting point for the Application of an observation guide on the proper management of Biosecurity Standards, among the most relevant results are; The application of biosafety standards was correctly given in 40%, the staff that does it is the group of nursing professionals, within the measures that are not properly applied is the management of hospital waste, among the standards applied correctly is Handling short pricks and handwashing.